Case report: Bilateral parotid abscess in a 54-day-old infant - Lilin Huang; Xiaole Yang; Shumei Peng; Ronghan Li (Frontiers Media S.A., 2023)
Acute parotid abscess (PA) is rare in children and is prone to occur in neonates or preterm infants with high-risk factors. Sporadic cases of unilateral PA have been reported in older children. Here, we report a case of a 54-day-old child who developed bilateral PA due to Staphylococcus aureus infection. The infant showed bilateral cervical lymphadenopathy initially following a 13-valent pneumococcal conjugate vaccine (PCV13). However, bilateral PA developed 6 h after he was diagnosed with lymphadenitis on Day 9 of illness. Rapid PA progression from cervical lymphadenitis is rare. He recovered quickly under treatment with appropriate antibiotics based on susceptibility testing and surgical incision and drainage.